Samlingens poesi - Brenna, Brita (Tidsskrift for kulturforskning, 2016)
Around the middle of the eighteenth century, natural history witnessed a burst of popularÂity in the conglomerate state of Denmark-Norway. Natural history was a composite and inclusive term, and was variously connected to or encompassed by terms like natural philosophy, natural knowledge, physical knowledge and not least economy. Natural history was also composite in terms of practices: Collecting, classifying, dissecting, drawing, writing of books and letters, socializing and travelling were different aspects of what was called natural history. Importantly collecting was entangled with the other practices to such a degree that collecting was a principal "way of knowing" in natural history in the eighteenth century. In this article I will investigate eighteenth century colleting practices through two lenses. First, I want to enquire how natural historical collecting and collections were used for bringing forth new knowledge in different ways. Secondly I am interested in how collecting can be seen as a way of knowing that straddled between the poetic and the rational. How is passion and rationality entangled in this initial period of scientific collecting? I follow how what can be termed Linnaean ways of knowing was practiced by some Danish-Norwegian natural historians, and how different ways of working with and in collections were developed. The query takes its offset from Bjarne Rogan’s work on nineteenth and twentieth century collectors to develop the notion of the "poetry of the collection"